Analisis Pengaruh Emisi GRK terhadap Indeks Kualitas Lingkungan Hidup (IKLH) di Kabupaten Bantul Tahun 2018-2025 - Yuyun Prihatining Rahmah (Jurnal Riset Daerah, 2026)
Efforts to reduce the rate of environmental damage and restore environmental quality continue to be carried out not only by the government but also by all elements of society. The Environmental Quality Index (IKLH) is information about the condition of the environment in an area at a certain time. Human efforts and activities are one of the factors that cause environmental problems. This study aims to analyze the effect of Greenhouse Gas emissions (emisi GRK) on the IKLH in Bantul Regency in 2018-2025. The variables used in this study are the calculation of the emisi GRK inventory in Bantul Regency in 2018-2025 as the X variable and the Environmental Quality Index (IKLH) in Bantul Regency in 2018-2025 as the Y variable. The analytical method used for this study is time series data regression. The results of the analysis show that emisi GRK significantly affect the IKLH in Bantul Regency. The data regression model formed is able to explain in Bantul Regency by 75.17%, and 24.83% is explained by other variables outside the model that are not included in the study.